Trichogramma parasitoids for control of Lepidopteran borers in Taiwan: species, life‐history traits and Wolbachia infections. (8th September 2015) - Wu, L. H.; Hoffmann, A. A.; Thomson, L. J.
Abstract: Trichogramma, polyphagous endoparasitoids of lepidopteran eggs, are used against a variety of crop pests throughout the world including those of sugar cane and corn in south‐eastern Asia. Their ability to be easily and economically reared on factitious hosts and their wide host range have contributed to their widespread use in pest control. The overall aim of this study was to select strains for eventual release in crop areas for control of lepidopteran borer pests of sugar cane and corn. To this end, we identified common Trichogramma species emerging from corn borer egg masses throughout south‐western Taiwan, compared their life‐history characteristics, assessed their thermal limits and identified the Wolbachia infection status of collected Trichogramma parasitoids. Trichogramma ostriniae was the most commonly collected species on corn, with occasional detection of T. chilonis and an unidentified species designated as T . sp. y . Although the sex ratio varied widely between sites, Wolbachia infection was detected only at a single site in one species ( T. ostriniae ). Wolbachia ‐infected T. ostriniae were tolerant to high temperature stress. Trichogramma chilonis had lowest fecundity of the three species tested, and a Wolbachia ‐infected T. ostriniae strain had lower fecundity than an uninfected strain. Given the limited availability of distribution and historical data for Trichogramma species in Taiwan, the current study provides a baseline for future work and also highlights the importance of accurately identifying species when establishing colonies of natural enemies for biocontrol.